1974-2024: cinquant’anni di scuola democratica? - Franceschini, Giuliano (Studi sulla Formazione/Open Journal of Education, 2024)
The Delegated Decress of 1974 profoundly reformed Italian schools. Their development and application are greatly affected by the political and cultural climate of the 1970s, they influence a large part of subsequent Italian school policy, up to the present day. From a pedagogical and didactic point of view, a series of important innovation are introduced: teaching collegiality, teaching planning, social management of the school, professional development and educational experimentation. The cultural and professional legacy left by the D.D. it is still very much alive today, although the political and social framework of reference has changed profoundly.